Report of four cases of Bardet-Biedl syndrome - Paulo Roberto Santos; Diego Levi Silveira Monteiro; Paulo Henrique Alexandre de Paula; Vicente Lopes Monte Neto (Brazilian Journal of Nephrology, 2014)
Bardet-Biedl syndrome is rare. Although its diagnosis depends on cardinal clinical manifestations which appear in childhood, we report four cases of Bardet-Biedl syndrome lately diagnosed in a dialysis center. Three cases were diagnosed in end-stage renal disease patients when they started maintenance hemodialysis, and one case was diagnosed through screening among hemodialysis patients' relatives. Although pediatricians have more opportunity to diagnose the syndrome, nephrologists are important during the treatment, since renal failure is the main cause of death among Bardet-Biedl syndrome patients. Moreover, late diagnosis of the syndrome among patients with end-stage renal disease can help to detect new cases through the screening among hemodialysis patients' relatives.